Powering a Learning Society During an Age of Disruption - Ra, Sungsup; Jagannathan, Shanti; Maclean, Rupert (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2021)
This open access book presents contemporary perspectives on the role of a learning society from the lens of leading practitioners, experts from universities, governments, and industry leaders. The think pieces argue for a learning society as a major driver of change with far-reaching influence on learning to serve the needs of economies and societies. The book is a testimonial to the importance of 'learning communities.' It highlights the pivotal role that can be played by non-traditional actors such as city and urban planners, citizens, transport professionals, and technology companies. This collection seeks to contribute to the discourse on strengthening the fabric of a learning society crucial for future economic and social development, particularly in the aftermath of the coronavirus disease.